A kind of adhesive for aluminum plastic film
By using a two-component adhesive in lithium battery packaging to form an adhesive layer between the aluminum foil layer and the polypropylene layer, the problems of poor electrolyte resistance and weak adhesion of the aluminum plastic film inner layer adhesive in the prior art are solved, and higher electrolyte resistance performance and safety are achieved.
Patent Information
- Application Number
- CN202310053724.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-02-03
AI Technical Summary
In lithium battery packaging, the inner layer adhesive has poor electrolyte resistance and weak adhesion, and is prone to quality problems such as aluminum-plastic film delamination.
Using a two-component binder, component A includes modified polyolefins, additives and solvents, component B includes isocyanates, additives and solvents, and a binder layer is formed between the aluminum foil layer and the polypropylene layer by dry composite technology.
It improves the electrolyte resistance and adhesion of aluminum-plastic film, reduces the risk of aluminum-plastic film delamination, and enhances the safety of lithium batteries.
Smart Images

Figure CN116082996B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum-plastic films for batteries, and particularly relates to an adhesive for aluminum-plastic films. Background Art
[0002] In recent years, with the high performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., people have begun to pursue high energy density of batteries. However, compared with the pursuit of high energy density of batteries, people pay more attention to the safety performance of batteries. In the past, most metal battery packaging materials used have the following disadvantages: it is difficult to follow the diversification of shapes and there are limitations in lightweight. Therefore, aluminum-plastic film is used as the outer packaging material of the battery to encapsulate the battery. Compared with traditional metal shell batteries, batteries encapsulated with aluminum-plastic film have the advantages of high energy density, easy processing into various shapes, and thinning and lightweighting.
[0003] Although aluminum-plastic film has given batteries many excellent properties, the existing aluminum-plastic film still has the following defects: Most of the existing aluminum-plastic films use polypropylene or modified polypropylene as the innermost layer, but polypropylene is a non-polar substance and has poor adhesion to aluminum. At present, there are two main bonding methods between CPP and aluminum foil layers: dry lamination and thermal lamination. Thermal lamination requires the use of an extruder. Although the final product has good electrolyte resistance and bonding properties, the equipment investment is large and it is difficult to make the aluminum-plastic film thin; while ordinary dry lamination uses conventional acrylic or polyurethane adhesives, which will make the bonding layer between the CPP layer and the aluminum foil layer poorly resistant to electrolytes, and it is easy to have quality problems such as aluminum-plastic film delamination.
[0004] In view of the above-mentioned shortcomings of the prior art, it is very necessary to develop a new adhesive to solve the problems of poor electrolyte resistance, weak bonding force, and easy delamination of the aluminum-plastic film in the inner layer of the lithium battery packaging aluminum-plastic film in the prior art. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide an adhesive for aluminum-plastic film.
[0006] In order to achieve the above purpose, one of the technical solutions of the present invention is: an adhesive for aluminum-plastic film, comprising component A and component B, wherein the component A comprises the following components by mass percentage: 10% to 30% of modified polyolefin, 1% to 5% of additives, and 65% to 89% of solvent, and the component B comprises the following components by mass percentage: 10% to 15% of isocyanate compound, 0.5% to 2% of additives, and 84.5% to 89.5% of solvent.
[0007] In a preferred embodiment of the present invention, the modified polyolefin is at least one of an acid / anhydride modified polyolefin or an acid / anhydride modified polyolefin elastomer.
[0008] Furthermore, the acid value of the modified polyolefin is 5-20 mgKOH / g.
[0009] Furthermore, the polyolefin in the acid / anhydride modified polyolefin includes polyethylene (PE) or polypropylene (PP), the polypropylene is preferably random polypropylene, and the polyolefin elastomer in the acid / anhydride modified polyolefin elastomer includes ethylene-octene copolymer (POE) or polypropylene and butadiene copolymer (PPB).
[0010] Furthermore, the acid is carboxylic acid, the acid anhydride is the anhydride of carboxylic acid, and the carboxylic acid includes maleic acid, itaconic acid and the like.
[0011] Furthermore, the melt index of the acid / anhydride modified polyolefin elastomer is 30-3000 g / 10 min, preferably 100 g / 10 min.
[0012] Furthermore, the acid / anhydride modified polyolefin elastomer is a mixture of amorphous polyolefin and alpha olefin, which are mixed in a mass ratio of 1:5-9:1. The obtained mixture has two melting points, the first melting point is 30-50°C, and the second melting point is 70-90°C.
[0013] Furthermore, the acid or / anhydride modification includes adding multifunctional auxiliary monomers such as TAIC (triallyl isocyanurate) and ST (styrene) to assist in acid modification.
[0014] In a preferred embodiment of the present invention, the modified polyolefin further comprises one or more of anhydride-modified polyolefin or polyolefin elastomer hydrolyzate, and the hydrolysis rate of the hydrolyzate is 10%-90%.
[0015] In a preferred embodiment of the present invention, the solubility parameter of the modified polyolefin in component A is 6-10 (cal / cm 3 ) 1 / 2 .
[0016] In a preferred embodiment of the present invention, the additive in the component A is one or more of anhydride monomers or acid-modified low molecular weight polyolefins.
[0017] In a preferred embodiment of the present invention, the solvent in component A includes a first solvent and a second solvent, the volume ratio of the first solvent to the second solvent is 7-19:1, and the first solvent and the second solvent include one or more of xylene, methylcyclohexane, butanone and ethanol.
[0018] Furthermore, it is characterized in that the first solvent is methylcyclohexane, and the second solvent is at least one of ethanol and butanone.
[0019] In a preferred embodiment of the present invention, the isocyanate in the B component includes one or more of HDI (hexamethylene diisocyanate), MDI (diphenylmethane diisocyanate), and IPDI (isophorone diisocyanate), preferably MDI.
[0020] In a preferred embodiment of the present invention, the additive in component B is an amine compound with the molecular formula:
[0021]
[0022] In a preferred embodiment of the present invention, the B component solvent includes one or more of methylcyclohexane, butanone, and ethyl acetate.
[0023] In a preferred embodiment of the present invention, the mass ratio of component A to component B is 20:1-5:1.
[0024] In a preferred embodiment of the present invention, the total solid content of the binder obtained by mixing the component A and the component B in a mass ratio is 10wt%-25wt%.
[0025] In order to achieve the above purpose, the second technical solution of the present invention is: a method for preparing an adhesive for aluminum-plastic film, comprising the following steps:
[0026] (1) The polyolefin and additives in component A are added to the first solvent in proportion, heated at 50-90° C. and stirred until the resin is evenly dispersed, and then the second solvent is added to obtain a transparent solution, which is sealed and stored;
[0027] (2) adding isocyanate and additives to the solvent in proportion, heating and stirring at 50-70° C. to dissolve to form component B, and storing in a sealed container;
[0028] (3) When using, mix components A and B evenly according to the proportion and use it quickly.
[0029] In order to achieve the above objectives, the third technical solution of the present invention is: a lithium battery encapsulation aluminum-plastic film, comprising a cast polypropylene layer, an aluminum foil layer and an adhesive layer formed between the cast polypropylene layer and the aluminum foil layer, wherein the adhesive layer is formed by coating the aluminum-plastic film with an adhesive.
[0030] In a preferred embodiment of the present invention, the lithium battery encapsulation aluminum-plastic film further comprises a nylon layer and an outer resin adhesive layer formed between the nylon layer and the aluminum foil layer.
[0031] In a preferred embodiment of the present invention, the cast polypropylene layer includes a heat-sealing layer, and the adhesive layer is formed between the surface of the heat-sealing layer and the inner surface of the aluminum foil layer.
[0032] In a preferred embodiment of the present invention, the cast polypropylene layer includes a heat-sealing layer and a core layer formed on the surface thereof, and the adhesive layer is formed between the surface of the core layer and the inner surface of the aluminum foil layer.
[0033] In a preferred embodiment of the present invention, the cast polypropylene layer includes a heat-sealing layer and a corona layer formed on the surface thereof, and the adhesive layer is formed between the surface of the corona layer and the inner surface of the aluminum foil layer.
[0034] In a preferred embodiment of the present invention, the cast polypropylene layer includes a heat sealing layer, a core layer formed on the surface thereof, and a corona layer formed on the surface of the core layer, and the adhesive layer is formed between the surface of the corona layer and the inner surface of the aluminum foil layer.
[0035] The method for preparing the aluminum-plastic film for lithium battery packaging comprises the following steps:
[0036] (1) coating an adhesive for lithium battery encapsulation aluminum-plastic film on the inner surface of the aluminum foil layer, and then drying;
[0037] (2) laminating the cast polypropylene layer to the inner surface of the aluminum foil layer obtained in step (1) by hot pressing to obtain an aluminum-plastic film semi-finished product;
[0038] (3) The aluminum-plastic film semi-finished product obtained in the step is aged and heated at 70-80° C. for 3-5 days to obtain the lithium battery encapsulation aluminum-plastic film.
[0039] In a preferred embodiment of the present invention, the coating amount of the adhesive for lithium battery packaging aluminum plastic film on the inner surface of the aluminum foil layer in step (1) is 2 to 3 g / m 2 .
[0040] In a preferred embodiment of the present invention, the temperature of the hot pressing compound in step (2) is 80-110° C., the aging temperature is 40-60° C., and the aging time is 5-7 days.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The adhesive polyolefin component provided by the present invention, such as polypropylene, has better solvent resistance and acid resistance due to its chemical inertness. The adhesive provided by the present invention is coated on the inner surface of the aluminum foil coated with a corrosion-resistant coating to form an inner adhesive layer, and then the aluminum foil layer with the inner adhesive layer is dry-compounded with the polypropylene BOPP layer, thereby improving the electrolyte resistance of the aluminum-plastic film.
[0043] 2. The adhesive of the present invention contains auxiliary ingredients such as isocyanate, so that it can cross-link with the hydrolyzed acid anhydride to form a network structure during the aging process, and the heat resistance and bonding performance are further improved, thereby improving the safety of the aluminum-plastic film soft-pack lithium battery.
[0044] 3. The adhesive for inner layer bonding provided by the present invention is a two-component adhesive, each component has a long shelf life, and is very convenient to prepare and use. Meanwhile, the solvents are all low-cost and low-toxic solvents, which saves solvent costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0046] Figure 1 This is a schematic diagram of the structure of the aluminum-plastic film prepared in Example 1 of the present invention.
[0047] Among them, 1-nylon layer, 2-first adhesive layer, 3-first corrosion-resistant layer, 4-aluminum foil layer, 5-second corrosion-resistant layer, 6-second adhesive layer, 7-heat sealing layer.
[0048] Figure 2 This is a sample picture after dry peeling test of the present invention. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is described in more detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments. The same reference numerals in the text always represent the same elements, and similar reference numerals represent similar elements.
[0050] In the description of the present invention, it is necessary to understand that the orientations or positional relationships indicated by terms such as “upper”, “lower”, “front”, “back”, “left”, “right”, “horizontal”, “vertical”, “top”, “bottom”, “inside” and “outside” are based on the orientations or positional relationships shown in the stereoscopic diagrams in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0051] Example 1
[0052] An adhesive for aluminum-plastic film is prepared by the following method:
[0053] (1) Preparation of component A: Maleic anhydride modified random polypropylene was used as the main agent, with an acid value of 5 mgKOH / g and a solubility parameter of 8.4 (cal / cm 3 ) 1 / 2 , the additive is maleic anhydride monomer, the addition amount is 1wt%, the first solvent is methylcyclohexane, the second solvent is ethanol, and the volume ratio of methylcyclohexane to ethanol is 10:1, maleic anhydride modified random polypropylene and the additive are added to the first solvent, heated and stirred at 70° C. until the resin is uniformly dispersed, and then the second solvent is added to obtain a transparent solution, and a component A with a solid content of 15wt% is prepared;
[0054] (2) Preparation of component B: the main isocyanate is HDI, the additive is an amine catalyst produced by Yizhou New Energy Co., Ltd., the addition amount is 1 wt%, the solvent is methylcyclohexane, HDI and the additive are added to the solvent, heated and stirred at 60° C. to dissolve to obtain component B with a solid content of 15 wt%;
[0055] (3) Preparation of AB two-component adhesive: The component A and component B prepared above were mixed at a mass ratio of 10:1 to prepare an AB two-component adhesive.
[0056] A lithium battery encapsulation aluminum-plastic film is prepared by the following method:
[0057] (1) The 40 μm aluminum foil layer is subjected to alkali washing, water washing, acid washing and neutralization, and water washing to obtain a clean aluminum foil layer;
[0058] (2) Using a coating machine, two different trivalent chromium treatment solutions BN-1 and BN-4 produced by Yizhou New Energy Technology Co., Ltd. are respectively coated on the inner and outer surfaces of the aluminum foil to form inner and outer corrosion-resistant coatings, namely, the first corrosion-resistant layer and the second corrosion-resistant layer, and then dried at 75°C. Then, using a coating machine, the AD1 adhesive produced by Yizhou New Energy Technology Co., Ltd. is coated on the outer surface of the aluminum foil as the first adhesive, and dried to obtain the first adhesive layer; using a laminating machine, hot-pressing nylon is laminated on the outer surface of the aluminum foil at 80°C, and the amount of adhesive is controlled so that the thickness of the first adhesive layer is 4 μm;
[0059] (3) The AB two-component adhesive is evenly applied on the inner surface of the aluminum foil layer to form a second adhesive layer. The coating amount of the adhesive on the inner surface of the aluminum foil layer is controlled to be 3g / m 2 , so that the thickness of the second adhesive layer is 4 μm; the PP layer (hot-melt resin) with a thickness of 80 μm is hot-pressed and laminated to the inner surface of the aluminum foil layer, and finally a semi-finished lithium battery aluminum-plastic film is obtained; the semi-finished product is aged and heated at 75°C for 4 days to obtain Figure 1 The lithium battery encapsulation aluminum-plastic film shown includes a laminate of a nylon layer 1, a first adhesive layer 2, a first corrosion-resistant coating 3, an aluminum foil layer 4, a second corrosion-resistant coating 5, a second adhesive layer 6 and a heat-sealing layer 7 stacked in sequence from outside to inside to form an aluminum-plastic composite material for solid-state battery encapsulation.
[0060] Example 2
[0061] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of the maleic anhydride modified random polypropylene in component A is 7 mgKOH / g.
[0062] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0063] Example 3
[0064] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of the maleic anhydride modified random polypropylene in component A is 9 mgKOH / g.
[0065] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0066] Example 4
[0067] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of the maleic anhydride-modified random polypropylene in component A is 5 mgKOH / g, the main isocyanate of component B is MDI, and the mass ratio of components AB is 20:3.
[0068] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0069] Example 5
[0070] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of the maleic anhydride-modified random polypropylene in component A is 7 mgKOH / g, the main isocyanate of component B is MDI, and the mass ratio of components AB is 20:3.
[0071] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0072] Example 6
[0073] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of the maleic anhydride-modified random polypropylene in component A is 9 mgKOH / g, the main isocyanate of component B is MDI, and the mass ratio of components AB is 20:3.
[0074] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0075] Example 7
[0076] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of the maleic anhydride-modified random polypropylene in component A is 9 mgKOH / g, the solid content of component A is 20 wt%, the main agent isocyanate in component B is HDI, the solid content of component B is 20 wt%, and the mass ratio of components AB is 20:3.
[0077] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0078] Example 8
[0079] A binder for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of the maleic anhydride modified random polypropylene of component A is 9 mgKOH / g, the solid content of component A is 20wt%, the main agent isocyanate of component B is MDI, the solid content of component B is 20wt%, and the mass ratio of components AB is 20:3.
[0080] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0081] Example 9
[0082] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of maleic anhydride-modified random polypropylene in component A is 9 mgKOH / g, the second solvent is acetone, the solid content of component A is 20wt%, the main agent isocyanate of component B is HDI, the solid content of component B is 20wt%, and the mass ratio of components AB is 20:3.
[0083] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0084] Example 10
[0085] A binder for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the acid value of maleic anhydride-modified random polypropylene in component A is 9 mgKOH / g, the second solvent is acetone, the solid content of component A is 20wt%, the main agent isocyanate of component B is MDI, the solid content of component B is 20wt%, and the mass ratio of components AB is 10:1.
[0086] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0087] Embodiment 11
[0088] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that TAIC-assisted maleic anhydride-modified random polypropylene is used as the main agent in component A, the acid value is 20 mgKOH / g, the solubility parameter is 8.8 (cal / cm 3 ) 1 / 2 The second solvent is acetone, the solid content of component A is 20wt%, the main isocyanate of component B is MDI, the solid content of component B is 20wt%, and the mass ratio of components AB is 10:1.
[0089] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0090] Example 12
[0091] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that the elastomer POE of maleic anhydride-modified polypropylene butadiene copolymer is used as the main agent in component A, the acid value is 9 mgKOH / g, the solubility parameter is 8.9 (cal / cm 3 ) 1 / 2 , The second solvent is acetone, the solid content of component A is 20wt%, the main agent isocyanate of component B is MDI, the solid content of component B is 20wt%, and the mass ratio of components AB is 10:1.
[0092] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0093] Comparative Example 1
[0094] An adhesive for aluminum-plastic film, the preparation method is the same as that of Example 1, except that unmodified random polypropylene is used as the main agent in component A, the acid value is 0 mgKOH / g, the solubility parameter is 8.4 (cal / cm 3 ) 1 / 2 The second solvent is acetone, the solid content of component A is 20wt%, the main isocyanate of component B is MDI, the solid content of component B is 20wt%, and the mass ratio of components AB is 10:1.
[0095] A lithium battery packaging aluminum-plastic film, the preparation method is the same as that of Example 1.
[0096] Ethylene carbonate, diethyl carbonate and dimethyl carbonate reagents are mixed in a ratio of 1:1:1, and lithium hexafluorophosphate is added to the mixture to prepare a solution with a lithium hexafluorophosphate substance amount of 1.0 mol / L, which is the electrolyte. The free acid content of the electrolyte is not higher than 50 parts per million. The purity of the above reagents is analytical grade.
[0097] Cut a strip of 100 mm long and 15 mm wide from each of the aluminum-plastic film prepared in Examples 1-10 and Comparative Example 1, inject electrolyte, submerge the strip, seal and place in an oven at 85°C, take out after 24 hours, rinse the residual electrolyte with water, wipe dry and measure the electrolyte peeling strength with a universal tensile machine and compare it with the peeling strength without electrolyte immersion. The results are shown in Table 1. It can be seen from the test results in the following table that the polyolefin without acid modification has no adhesion, and the adhesion of the modified polyolefin increases with the increase of acid value, reaching the maximum when the acid value is 9 mgKOH / g, and then basically maintains the same. The curing effect of benzene ring isocyanate MDI is better than that of chain isocyanate HDI, and the electrolyte peeling strength and dry peeling strength both reach the industry standard.
[0098] Table 1 Peel strength test results
[0099]
[0100] The above embodiments are merely optimized implementation methods of the present invention, which are used to illustrate the principles and effects of the present invention, but are not used to limit the present invention. It should be noted that any person skilled in the art may modify the above embodiments without violating the spirit and scope of the present invention, and such modifications shall also be regarded as the protection scope of the present invention.
Claims
1. An adhesive for aluminum-plastic film, characterized in that: The invention comprises component A and component B, wherein the component A comprises the following components according to mass percentage: 10% to 30% of modified polyolefin, 1% to 5% of additives, and 65% to 89% of solvent, and the component B comprises the following components according to mass percentage: 10% to 15% of isocyanate compound, 0.5% to 2% of additives, and 84.5% to 89.5% of solvent; the additive in the component A is one or more of anhydride monomers or acid-modified low molecular weight polyolefins; the additive in the component B is an amine compound, and the molecular formula is:
2. The adhesive for aluminum-plastic film according to claim 1, characterized in that: The modified polyolefin is at least one of an acid / acid anhydride modified polyolefin or an acid / acid anhydride modified polyolefin elastomer.
3. The adhesive for aluminum-plastic film according to claim 2, characterized in that: The acid value of the modified polyolefin is 5-20 mgKOH / g.
4. The adhesive for aluminum-plastic film according to claim 2, characterized in that: The polyolefin in the acid / acid anhydride modified polyolefin includes PP or PE, and the polyolefin elastomer in the acid / acid anhydride modified polyolefin elastomer includes POE or PPB.
5. The adhesive for aluminum-plastic film according to claim 2, characterized in that: The melt index of the acid / anhydride modified polyolefin elastomer is 30-3000g / 10min. The acid / anhydride modified polyolefin elastomer is a mixture of amorphous polyolefin and alpha olefin. The amorphous polyolefin and the alpha olefin are mixed in a mass ratio of 1:5-9:
1. The obtained mixture has two melting points, the first melting point is 30-50°C, and the second melting point is 70-90°C.
6. The adhesive for aluminum-plastic film according to claim 2, characterized in that: The acid is a carboxylic acid, the acid anhydride is an acid anhydride corresponding to the carboxylic acid, the carboxylic acid includes itaconic acid or maleic acid, and the acid anhydride includes itaconic anhydride or maleic anhydride.
7. The adhesive for aluminum-plastic film according to claim 2, characterized in that: The acid / anhydride modification includes adding TAIC or ST multifunctional auxiliary monomer to assist.
8. The adhesive for aluminum-plastic film according to claim 1, characterized in that: The modified polyolefin also includes one or more of anhydride-modified polyolefin or polyolefin elastomer hydrolyzate, and the hydrolysis rate of the hydrolyzate is 10%-90%.
9. The adhesive for aluminum-plastic film according to claim 1, characterized in that: The solubility parameter of the modified polyolefin is 6-10 (cal / cm 3 ) 1 / 2 .
10. The adhesive for aluminum-plastic film according to claim 1, characterized in that: The solvent in the A component includes a first solvent and a second solvent, the volume ratio of the first solvent to the second solvent is (7-19):1, and the first solvent and the second solvent include one or more of xylene, methylcyclohexane, butanone and ethanol; the solvent in the B component includes one or more of methylcyclohexane, butanone and ethyl acetate, and the isocyanate in the B component includes one or more of HDI, MDI and IPDI.
11. The adhesive for aluminum-plastic film according to claim 1, characterized in that: The mass ratio of the component A to the component B is 20:1-5:1, and the total solid content of the binder after the component A and the component B are mixed according to the mass ratio is 10wt%-25wt%.
12. A lithium battery encapsulation aluminum-plastic film, characterized in that: The invention comprises a cast polypropylene layer, an aluminum foil layer and an adhesive layer formed between the cast polypropylene layer and the aluminum foil layer, wherein the adhesive layer is formed by coating the adhesive for aluminum-plastic film according to any one of claims 1 to 11.
13. A method for preparing an adhesive for aluminum-plastic film according to any one of claims 1 to 11, characterized in that: The steps include: (1) The polyolefin and additives in component A are added to the first solvent in proportion, heated and stirred at 50-90° C. until the resin is evenly dispersed, and then the second solvent is added to obtain a transparent solution; (2) adding isocyanate and additives to a solvent in proportion, heating and stirring at 50-70° C. to dissolve to prepare component B; (3) Mix component A and component B evenly according to the proportion and use it quickly.
Citation Information
Patent Citations
Aluminum-plastic film inner layer adhesive, preparation method thereof and application of aluminum-plastic film inner layer adhesive in aluminum-plastic film
CN115181519A